2003
DOI: 10.1177/0885066602239122
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the α2-Adrenoceptor Agonist Dexmedetomidine in Postsurgical Sedation in the Intensive Care Unit

Abstract: Dexmedetomidine was evaluated for sedation of 401 post-surgical patients in this double-blind, randomized, placebo-controlled, multicenter trial. Dexmedetomidine or saline was started on arrival in the intensive care unit (ICU) (1.0 mcg/kg for 10 minutes), then titrated at 0.2 to 0.7 mcg/kg/h to effect. Patients could be given propofol if necessary. Morphine was administered for pain. Sixty percent of the dexmedetomidine patients required no other sedative to maintain an RSS > or = 3; 21% required < 50 mg prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
198
2
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(218 citation statements)
references
References 37 publications
13
198
2
5
Order By: Relevance
“…Confusion, cited as a common problem for other traditional sedatives, has not been described for DEX as it does not depend primarily on activation of the g aminobutyric acid system. 23 Although rapid recovery without residual sedation is a major objective in out-patient adult surgery, a certain degree of sedation after pediatric surgery might represent a desired effect by the parents. A calm and sedated child during the early post-operative period could decrease the parent's anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Confusion, cited as a common problem for other traditional sedatives, has not been described for DEX as it does not depend primarily on activation of the g aminobutyric acid system. 23 Although rapid recovery without residual sedation is a major objective in out-patient adult surgery, a certain degree of sedation after pediatric surgery might represent a desired effect by the parents. A calm and sedated child during the early post-operative period could decrease the parent's anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…DXM is a highly selective 2-adrenoreceptor agonist approved as intravenous sedative and adjuvant to anesthesia. DXM when used intravenously during anesthesia reduces opioid and inhalational anesthetics requirements [21,22] . Compared with clonidine a 2-adrenoreceptor agonist, the affinity of DXM to 2 receptors has been reported to be 10 times more than clonidine [23] , moreover, Kalso et al [5] and Post et al [24] reported a 1:10 dose ratio between intrathecal DXM and clonidine in animals.…”
Section: Discussionmentioning
confidence: 99%
“…Its affinity for binding to the alpha-2/alpha-1 receptor is 1300:1 compared with 39:1 for clonidine [3,4]. It has potent sedative analgesia-sparing properties [5 -11].…”
Section: Introductionmentioning
confidence: 99%